Coherent Control of the Nonlinear Emission of Single Plasmonic Nanoantennas by Dual‐Beam Pumping (Advanced Optical Materials 20/2022). Issue 20 (18th October 2022) - Di Francescantonio, Agostino; Locatelli, Andrea; Wu, Xiaofei; Zilli, Attilio; Feichtner, Thorsten; Biagioni, Paolo; Duò, Lamberto; Rocco, Davide; De Angelis, Costantino; Celebrano, Michele; Hecht, Bert; Finazzi, Marco
Abstract : An asymmetric plasmonic nanoantenna mediates the nonlinear mixing between ultrashort infrared laser pulses at frequency ω and 2ω. The third harmonic at ω + ω + ω and the sum frequency at ω + 2ω are coherent and degenerate at the visible frequency 3ω. Consequently, a relative time delay between the ω and 2ω pumps brings a strong modulation of the power at 3ω due to interference. This phase‐dependent modulation, as presented in article number 2200757 by Michele Celebrano and co‐workers, realizes an ultrafast coherent control scheme of nonlinear emission.